2017
DOI: 10.1038/s41598-017-02357-0
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA LINC00152 is essential for cell cycle progression through mitosis in HeLa cells

Abstract: In recent years, long non-coding RNA (lncRNA) research has identified essential roles of these transcripts in virtually all physiological cellular processes including tumorigenesis, but their functions and molecular mechanisms are poorly understood. In this study, we performed a high-throughput siRNA screen targeting 638 lncRNAs deregulated in cancer entities to analyse their impact on cell division by using time-lapse microscopy. We identified 26 lncRNAs affecting cell morphology and cell cycle including LINC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 88 publications
(115 reference statements)
4
51
1
1
Order By: Relevance
“…We applied functional siRNA screening for lncRNAs with a loss‐of‐viability phenotype in HCC. The results of the screening are in excellent accordance with other studies: the lncRNA genes HOX transcript antisense RNA, long intergenic non–protein coding RNA 152, Pvt1 oncogene, and HCC up‐regulated lncRNA are known to be important for cancer cell viability and exhibited high negative z scores (loss of viability) in the screen. Hence, this data set provides a useful resource for subsequent research on viability‐associated lncRNAs in HCC.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We applied functional siRNA screening for lncRNAs with a loss‐of‐viability phenotype in HCC. The results of the screening are in excellent accordance with other studies: the lncRNA genes HOX transcript antisense RNA, long intergenic non–protein coding RNA 152, Pvt1 oncogene, and HCC up‐regulated lncRNA are known to be important for cancer cell viability and exhibited high negative z scores (loss of viability) in the screen. Hence, this data set provides a useful resource for subsequent research on viability‐associated lncRNAs in HCC.…”
Section: Discussionsupporting
confidence: 86%
“…To derive a broader set of cancer‐associated lncRNAs and to design a library of siRNAs against these candidates as a versatile tool to dissect lncRNAs in cancer, this data set was merged with results from two other cancer entities, breast ductal carcinoma and lung adenocarcinoma (all data deposited in the National Center for Biotechnology Information’s Gene Expression Omnibus). The analysis of this integrated data set yielded a total of 638 significantly dysregulated lncRNAs, mostly up‐regulated, which were used for the siRNA library design as described . An RNAi‐mediated knockdown screen of these 638 candidate genes was done, and the impact on cellular viability in two established HCC cell lines (HLE and Huh‐7) was determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated that the knockdown of linc00152 by a prometaphase arrest can indirectly induce the apoptosis of transfected HeLa cells, further implying that linc00152 may participate in the cell cycle by interacting with proteins related to the M phase; however, the mechanism mediating this interaction remains unclear. 54 Other studies have also suggested that linc00152 affects the cell cycle. 27,29,34,36,54…”
Section: Overexpression Of Linc00152 Enhances Cell Proliferation Imentioning
confidence: 99%
“…Nötzold et al detected upregulated linc00152 expression in lung, liver, and breast cancers, but not in Burkitt's lymphoma. A cell viability assay indicated that inhibited linc00152 expression can disrupt cell proliferation.…”
Section: Molecular Functions and Mechanisms Of Linc00152 In Human Tumorsmentioning
confidence: 99%